Correlation of Media and Parents Role to Adolescent Sexual Behavior - Adelse Prima Mulya; Mamat Lukman; Desy Indra Yani (Journal of Nursing Care, 2020)
Adolescent sexual behavior affected by many factors such as the lack of parents' role in supervising Adolescents and information from electronic media that is less educative so that high school Adolescents in Bandung are encouraged to engage in risky behavior. The purpose of this study is to see how correlations media roles and a parent’s role with adolescent sexual behavior in an SMA Bandung. This research was quantitative, used an analytic method with a cross-sectional approach. The population in this study was all students of class X and XI in an SMA Bandung, amounting to 580 people. Samples were count using an estimated absolute precision sample formulas with a total of 246 students. The data collected use three pieces of the questionnaire including Adolescent sexual behavior questionnaire, media role, and parent’s role questionnaires. All of them were passed reliability and validity checked. Data were analyzed using Chi-square. The results showed, the role of parents has a correlation with adolescent sexual behavior and also the role of Media, it has correlation too. It is recommended to school staff, parents, and high school students, unwell adolescent behavior is our responsibility together. Schools can make regulations regard this, parents can increase the control to them. Besides, it can enhance the adolescent’s health, and it would be a better future for them.